The Influence of Digital Economy Development on the Income of Micro, Small, and Medium Enterprises in East Alok District - Kristianus Pana; Wilhelmina Mitan; Paulus Libu Lamawitak (International Publisher (YAPENBI), 2024)
This study aims to determine the influence of digital economy development on the income of Micro, Small, and Medium Enterprises in East Alok District, Sikka Regency. This research explores data sourced from Micro, Small, and Medium Enterprises (MSMEs) in Sikka Regency because Sikka Regency has many office facilities, schools, and shops, and is a center for culinary tourism in East Alok District. In this research, the author uses quantitative research. The population in this study is MSMEs in East Alok District, Sikka Regency which totals 1,548 MSMEs. In this study, the size of the sample was determined using the Slovin formula so that the number of samples to be used as samples in this study was 94 MSME Units. The purposive sampling technique is used to determine the type of sample to be used in this study. The results of the study show that the Digital Economy affects the income of MSME actors in Alok District, Sikka Regency. By leveraging digital technology, individuals and organizations can improve efficiency, reach more customers, and develop new, sustainable revenue streams.